Pengembangan desain sarana pengembalian buku di ruang baca perpustakaan Kota Yogyakarta - Kristian Oentoro; Laurensius Windy O.H.; R. Tosan Tri Putro (Institut Seni Indonesia Yogyakarta, 2017)
Yogyakarta city library applied an open access service system, in which the library users were given access to independently find and take the books in collection shelves. Those users were also asked to return the finished books to the returning books medium in the form of trolleys. Later these books in the trolleys would be returned by the librarians scheduled for shelving duty. Observation result showed that there are a lot of unreturned books because the trolleys of the returning mediums are too full. Librarian also faced many difficulties in classifying the book stacks before returned to the collection shelves because of their messy state. According to the design study and development employing front- end process method, process (Karl & Steven, 2008), this problem could be solved by developing design concept for books returning mediums in the form of shelves contained colors and book codes information according to the standard of Yogyakarta city library. The result design prototype trial showed the increasing library users’ interest to return the finished books to the returning books medium according to the color and code information. It would greatly help the librarians in classifying the books before the re-organizing in the collection shelves. Design development of the returning books medium would also open the opportunity to optimize the temporary flow of returning books which would be easily found by the other library users before the shelving schedule.Keywords: library, open access, book shelf, librarian, library user